Graphical Password Authentication Using Cued Click Points - Greeshma, PY; Joe, Jerry; Jisna, VA; Krishnapriya, MA; Saranya, TG (International Journal of Computer Sciences and Engineering, 2014)
Cued Click points (CCP) is a click-based graphical password scheme, a cued-recall graphical password technique. Users Click on one point per image for a sequence of images. Performance was very good in terms of speed, accuracy, and number of errors. Users preferred CCP to Pass point, saying that selecting and remembering only one point per image was easier, and that seeing each image triggered their memory of where the corresponding point was located, CCP also provides greater security than Pass Points because the number of images increases the workload of attackers.